Zaruelang Iloko : mga salin sa Filipino kalakip ang orihinal na Iloko - Rosal, Mario G.R.; Crisolog, Mena Pecson. Neneng; Gurrrero,Pascual Agcaoili; Paat, Barbara P. Siacti; Daguiti agpaspasucmon basi (Loyola Hiegths, QC : Ateneo de Manila University Press, 1993)
Filipino and Iloko text
Includes music score
Keywords: Iloko drama